2002
DOI: 10.1088/0953-8984/14/50/313
|View full text |Cite
|
Sign up to set email alerts
|

Raman-active modes of porous gallium phosphide at high pressures and low temperatures

Abstract: Porous gallium phosphide (GaP) with a honeycomb-like morphology and a skeleton relative volume concentration c = 0.7 was investigated by Raman spectroscopy under pressure up to 10 GPa at T = 5 K. The porous samples were prepared by electrochemical etching. The transverse optical (TO) and longitudinal optical (LO) mode frequencies were found to shift with pressure similarly to those of bulk GaP. As in bulk GaP, the TO feature of the porous GaP exhibits a pressure-induced narrowing which is interpreted in terms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 41 publications
1
10
0
Order By: Relevance
“…8. However, two modes were observed and attributed to the F-T and F-L Fröhlich modes in Raman measurements of por-GaP with a honeycomblike morphology under pressure up to 10 GPa and at T D 5 K. 92 A surface-related phonon mode in porous GaP at 397 cm 1 was first observed by Tiginyanu et al 93 and interpreted in terms of a Fröhlich mode on the basis of an effective medium approach. 94 It was shown that its wavenumber decreases with increasing anodization current.…”
Section: Measurements On Porous Compound Semiconductorsmentioning
confidence: 96%
“…8. However, two modes were observed and attributed to the F-T and F-L Fröhlich modes in Raman measurements of por-GaP with a honeycomblike morphology under pressure up to 10 GPa and at T D 5 K. 92 A surface-related phonon mode in porous GaP at 397 cm 1 was first observed by Tiginyanu et al 93 and interpreted in terms of a Fröhlich mode on the basis of an effective medium approach. 94 It was shown that its wavenumber decreases with increasing anodization current.…”
Section: Measurements On Porous Compound Semiconductorsmentioning
confidence: 96%
“…Some of the areas of current interest are (i) photonic polaritonic materials [5], (ii) left handed materials [6], (iii) porous semiconductor materials [7,8], (iv) microcavity polaritons [9], and (v) those associated with acoustic modes in a piezoelectric material [10,11]. Some of these phenomena are made use of in devices for supporting spontaneous emission, for projecting light along a specific path in novel laser geometry and in efficient frequency conversion [12][13][14] and so on.…”
Section: Introductionmentioning
confidence: 99%
“…However, the studies on Qwire and QDOT systems are sparse [18,19]. After the path breaking work of Canham [20], several authors have studied the optical properties of the porous semiconducting materials [7,8]. Raman spectroscopy has proved to be the most successful technique for such studies.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations